PENGARUH PROFITABILITAS, LEVERAGE, FIRM SIZE, EARNINGS POWER, DAN TAX AVOIDANCE TERHADAP MANAJEMEN LABA - Defina Yuliastuti; Ida Nurhayati (Jurnal GeoEkonomi, 2023)
The purpose of this research is to examine and analyze the effect of profitability, leverage, firm size, earnings power, and tax avoidance on earnings management in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. This study uses a purposive sampling method in taking predetermined criteria. Where there are 420 sample companies that meet the criteria in this study. The analysis technique in this study used multiple linear regression analysis with the SPSS version 21 application. The results showed that profitability and tax avoidance had no effect on earnings management, while leverage, firm size, and earnings power had a significant positive effect on earnings management.